Packet sniffer & analyzer / Ong Khoon Kok - Ong , Khoon Kok (2000)
The communication of network is a complex process which cannot be seen by human beings. Even a computer that sit on a network can only knows the conversation within itself and others computer it talk to but not others computers· conversation that it didn't take part. Furthermore, the communication in network can be viewed as traffic which always triggers a lot of unsolved problems for computers to "talk. Therefore, to solve the problems we need to exactly know what really happened inside the network traffic. A variety of sniffing tools are invented for these purpose. All of these tools have the basic capability that is to capture all frames transmitted through the network without "talk'' to others. Every frames transmitted reveal everything about the information how it transmit. from ''here it direct to. What rules (protocol) it used and what data it carried. Therefore the captured frames can then process by the programs to interpret into a meaning data that helps the user in multiple purposes. Besides the gathering of these packets will provide another means of useful information about the entire network traffic statistic. Sniffer has the great potential to further develop for more powerful tools like network monitor, security tools or scanning tools that are intelligent to report an alert to human or automatically take the right action to prevent a certain threat for the network without intervention by humans or at least with minimum human loads. The development of these tools has it limitations with different platforms. This is because different operating system operates differently, the sniffer program actually communicate with the kernel system of operating system and the network adapter's driver in order to tum the network card into promiscuous mode.